2012
DOI: 10.2215/cjn.07420711
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Dialysis Withdrawal

Abstract: Summary Background and objectives Dialysis withdrawal (DW) in patients with ESRD is increasing in importance. This study assessed causes of death and risk factors for DW in Australia and New Zealand in the first year of dialysis. Design, setting, participants, & measurements This retrospective observational cohort study included all adult Australians and New Zealanders beginning renal replacement therapy in 1999–2008. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 29 publications
5
61
0
Order By: Relevance
“…Additional findings in our study include previously reported risk factors for dialysis withdrawal, such as increasing age, female sex, and white race (4,5,7). The reasons that nonwhite patients withdraw less often are unclear; however, it is likely that religious and cultural beliefs play a significant role (20).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Additional findings in our study include previously reported risk factors for dialysis withdrawal, such as increasing age, female sex, and white race (4,5,7). The reasons that nonwhite patients withdraw less often are unclear; however, it is likely that religious and cultural beliefs play a significant role (20).…”
Section: Discussionsupporting
confidence: 59%
“…In our study, modality type was not associated with withdrawal, but dialysis at home, in a community setting, and in an urban center were associated with fewer withdrawals, perhaps because of increased home and community supports. In contrast, Chan et al (7) found that patients undergoing hemodialysis were more likely to withdraw than those undergoing peritoneal dialysis. The authors surmised that the greater sense of personal control over treatment facilitated adherence to treatment, leading to less withdrawal; however, they could not rule out selection bias and unmeasured confounders leading to this result because frail patients are more likely to begin renal replacement therapy with hemodialysis.…”
Section: Discussionmentioning
confidence: 91%
“…According to Australian registry data, for every new case that receives dialysis another patient with ESKD dies without having received it [52]. Further, for those who do commence dialysis, around 37% will die via withdrawal from treatment [53]. For these patients, medical management may involve a shift from efforts to prolong life to a more supportive/palliative care model focusing on care, quality of life and symptom control.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have sought to risk‐stratify dialysis initiators for all‐cause mortality, while others have examined the factors associated with dialysis withdrawal . However, few if any studies have rigorously examined early withdrawal in incident dialysis patients.…”
Section: Introductionmentioning
confidence: 99%